INTERLEUKIN 28 RECEPTOR GENE ALPHA IL28RA AND PSORIASIS: ASSOCIATION WITH DISEASE SEVERITY AND AGE AT ONSET - E. S. Galimova; E. K. Khusnutdinova (Медицинская иммунология)
Molecular basis still remains unclear for psoriasis, a chronic inflammatory skin disease. It biological features are presented by abnormal differentiation of epidermal keratinocytes, overgrowth and dilation of blood vessels, and leukocyte infiltration of dermal and epidermal skin layers. These events appear to be driven, mainly, by various cytokines and chemokines released by activated T cell populations. The aim of this replication study was to determine, whether the rs4649203 SNP of IL28RA gene is associated with susceptibility to psoriasis. A total of 341 patients with psoriasis and 407 matched healthy controls were enrolled to carry out a case control study. Genotyping was performed using a Real-Time PCR assay. Our preliminary data suggest that the polymorphism located in IL28RA gene, known to be related to inflammatory and immunity processes, showed an association with patients’ age at onset and the disease severity. The results of this study are promising, with respect to development of a personalized approach to psoriasis treatment.